Controle da podridão azeda em frutos cítricos através de métodos alternativos - Machado, Bianca Ikari (2018)
Fungicides such as Thiabendazole and Imazalil are commonly used for the control of post-harvest diseases in citrus, presenting a good control especially on blue mold (Penicillium italicum) and green mold (Penicillium digitatum). On the other hand, for the sour rot caused by the Geotrichum citri-aurantii that occurs, also, in the post-harvest of citrus there is no sustainable method or, a chemical control that is registered under the conditions of Brazil. The restriction of the use of chemical products due to phytotoxicity, residual effects, action spectrum, obtaining of resistant strains from pathogen and its harmful effects have stimulated the reduction of its use and the adoption of alternative methods. Specific practices, such as biological control or the use of natural products, aim at maintaining the equilibrium of the agroecosystem, so that the plant in the presence of the pathogen does not suffer significant economic damages. In view of the above, the objective of this work was to investigate different alternative methods for the control of sour rot. For this, in vitro and in vivo tests were carried out with fruits of Pêra sweet orange and Murcott tangor, where they were submitted to treatments with immersion (heat treatment, chitosan and guazatine fungicide at different doses) or pipetting (suspension of yeast Sporobolomyces koalae), associated or not. In vitro tests showed the potential of the guazatine fungicide to control G. citri-aurantii, providing 100% inhibition in the mycelial growth. The use of half of dose of the fungicide associated with S. koalae yeast (ACBL-42) was the best control for sour rot in Pêra sweet orange and Murcott tangor fruits, with 100% healthy fruits and did not affect the quality of the fruits. Chitosan, as a natural product, was only effective in the reducing of size of the lesions caused by G. citri-aurantii, and did not decrease the number of diseased fruits, and this effect was only observed when the fruits of Pêra sweet orange and Murcott tangor were treated in a curative way. The prevent treatment with yeast alone showed efficient control of disease in tangor Murcott. The heat treatment (52ºC/three minutes) combined or not with biological method (yeast) or natural product (chitosan) did not present effective control of the disease, when applied in citrus fruits.